2020
DOI: 10.1021/acs.est.0c03982
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models for Estrogen Receptor Bioactivity and Endocrine Disruption Prediction

Abstract: The U.S. Environmental Protection Agency (EPA) periodically releases in vitro data across a variety of targets, including the estrogen receptor (ER). In 2015, the EPA used this data to construct mathematical models of ER agonist and antagonist pathways to prioritize chemicals for endocrine disruption testing. However, mathematical models require in vitro data prior to predicting estrogenic activity, but machine learning methods are capable of prospective prediction from molecular structure alone. The current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 59 publications
4
44
0
Order By: Relevance
“…We have shown that ECFP6 fingerprints compare favorably with other descriptors. 54 We have compared Assay Central with other machine learning methods for a relatively small number of targets such as drug-induced liver injury, 52 rat acute oral toxicity, 53 estrogen receptor, 54,55 androgen receptor, 56 GSK3β 57 M. tuberculosis, 58,59 non-nucleoside reverse transcriptase, and whole cell HIV. 60 In general, we have found from our earlier studies that while DNN generally performed the best for five-fold cross-validation, with external test sets, this superiority was not observed and generally Assay Central performed comparably with SVM classification or DNN.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that ECFP6 fingerprints compare favorably with other descriptors. 54 We have compared Assay Central with other machine learning methods for a relatively small number of targets such as drug-induced liver injury, 52 rat acute oral toxicity, 53 estrogen receptor, 54,55 androgen receptor, 56 GSK3β 57 M. tuberculosis, 58,59 non-nucleoside reverse transcriptase, and whole cell HIV. 60 In general, we have found from our earlier studies that while DNN generally performed the best for five-fold cross-validation, with external test sets, this superiority was not observed and generally Assay Central performed comparably with SVM classification or DNN.…”
Section: ■ Discussionmentioning
confidence: 99%
“…29 This study may be enlightening as it echoes our earlier findings on individual datasets after extensive manual curation. 52,53,[55][56][57][58][59][60]82 It also goes some way further in using external validation with these methods for toxicology and drug discovery properties. Now that we have generated such a vast array of over 5000 machine learning models, it presents opportunities for using them for predicting the potential of new molecules to interact with targets of interest or avoiding others (such as PXR and hERG) that may result in undesirable effects.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this concern, a discriminator for the multilayer perceptron (MLP) was designed and constructed to be attached for assessment. Applying supervised machine learning classifiers is a well-accepted strategy in virtual screening, with successful stories reported [ 64 , 65 , 66 , 67 ]. The inclusion of the discriminator further closes the in silico design-test loop in this practice.…”
Section: Resultsmentioning
confidence: 99%
“…Assay Central TM is proprietary software for curating high-quality datasets, generating Bayesian machine learning models with extended-connectivity fingerprints (ECFP6) generated from the CDK library 56 , and making prospective predictions of potential for bioactivity 1, 51-53, 57-64 . We have previously described this software in detail 1,[51][52][53][57][58][59][60][61][62][63][64] as well as the interpretation of prediction scores 54,65 , and the metrics generated from internal five-fold cross-validation used to evaluate and compare predictive performances. These metrics include, but are not limited to, ROC score 51 , Cohen's kappa (CK) 66,67 , and Matthew's correlation coefficient (MCC) 68 as described by us previously.…”
Section: Machine Learning -Assay Central Tmmentioning
confidence: 99%